فعالية طريقة التدريس بالمقاربة بالكفاءات حسب نظرة أساتذة مرحلة التعليم المتوسط بمتوسطات منطقة تامنغست أنموذجا - بن عبد السلام, عبد الله; حمدي, أم الخير (جامعة الوادي - University of Eloued, 2021)
هدفت الدراسة الى معرفة مدى فعالية طريقة التدريس بالمقاربة بالكفاءات حسب نظرة أساتذة مرحلة التعليم المتوسط بمتوسطات منطقة تامنغست أنموذجا وتمت الدراسة على عينة مكونة من 30 أستاذ يدرسون مواد مختلفة ، اللغة العربية ،الرياضيات ،التاريخ والجغرافيا، العلوم الفيزيائية والتكنولوجية وعلوم الطبيعة والحياة ، وقام الباحثان بتصميم إستبيان تقديري لقياس مدى فعالية طريقة التدريس بالمقاربة بالكفاءات يضم بنود حول بناء التعلمات( الوضعيات) وإدماجها وتقويم الأنشطة ومدى تحقيق الكفاءات المرجوة وخلصت الدراسة إلى أن طريقة التدريس بالمقاربة بالكفاءات حسب رأي أساتذة التعليم المتوسط فعالة وهادفة وتحقق المقاصد التعليمية المرجوة وتمتاز بالشمولية إلا أنها أقل وضوحا وتمس أنشطتها المقترحة في المنهاج( الوضعيات) الجوانب النظرية والتطبيقية وتحقق إشباعات المتعلم النفسية والمعرفية وتساهم في زرع روح المبادرة وأنها معيارية وليست مطلقة، ويرون أن طريقة التقويم (المعارف ،المهارات والقدرات) تحقق مقاصد الكفايات المراد تجسيدها ويؤدي التدريس بالمقاربة بالكفاءات إلى الإدماج بين التعلم والتعليم والتقويم. The study aimed to find out the effectiveness of the teaching method with the competency approach according to the perception of the professors of the intermediate education stage in the tamanghasset region averages as a model. The study was carried out on a sample of 30 teachers studying different subjects, Arabic language, mathematics, history and geography, physical and technological sciences and natural and life sciences, and the two researchers designed a questionnaire My appreciation for measuring the effectiveness of the teaching method using the competency approach includes items on building the learning (postures) and their incorporation and evaluation of activities and the extent to which the desired competencies are achieved. The study concluded that the method of teaching with the competency approach according to the opinion of intermediate education teachers is effective and purposeful and achieves the desired educational objectives and is characterized by comprehensiveness, but it is less clear and affects its activities The proposed curriculum (positives) has theoretical and practical aspects and achieves the psychological and cognitive satisfactions of the learner and contributes to implanting the spirit of initiative and it is standard and not absolute, and they see that the evaluation method (knowledge, skills and abilities) achieves the objectives of the competencies that are to be embodied, and teaching with competencies leads to the integration between learning, education and evaluation.
The effectiveness of the teaching method with the approach to competencies according to the perception of the teachers of the intermediate education stage with the average of the Tamanghasset region as a model
مقال
Keywords: مقاربة بالكفاءات؛ تعلمات ؛وضعيات؛ إدماج؛ أنشطة؛ تقويم; Approach with competencies, instructions; positions, inclusion, activities, evaluation